COVID-19 vaccine acceptance among healthcare workers in India: Results from a cross-sectional survey. - Kayur Mehta; Baldeep K Dhaliwal; Sanjay Zodpey; Stacie Loisate; Preetika Banerjee; Paramita Sengupta; Madhu Gupta; Anita Shet (Public Library of Science (PLoS), 2022)
Remarkable scientific progress has enabled expeditious development of effective vaccines against COVID-19. While healthcare workers (HCWs) have been at the frontline of the pandemic response, vaccine acceptance amongst them needs further study. We conducted a web-based survey to assess vaccine acceptance among HCWs in India between January and February 2021, shortly after the launch of India's vaccination campaign. Descriptive statistics were used to examine respondent demographics and Likert scale responses. Binomial logistic regression analyses were used to identify factors associated with vaccine acceptance. The survey yielded 624 respondents from 25 states and five union territories in India; 53.5% were male, and median age was 37 years (IQR 32-46). Amongst all respondents, 84.1% (525/624) supported COVID-19 vaccines, and 63.2% (141/223) of those unvaccinated at the time of survey administration were willing to accept a vaccine. Trust in government sources, healthcare providers or scientific journal articles for COVID-19 related information was reported by 66.8%, while confidence in social media for this information was reported by only 4.5%. Amongst those who had not yet received a COVID-19 vaccine, factors independently associated with vaccine acceptance included age (aOR 3.50 [95% CI, 1.04-11.76] for those above 45 years compared to younger HCWs aged 18-29 years), belief in vaccine effectiveness and safety (aOR 3.78 [95% CI 1.15-12.38]), and provision of free/no-cost vaccine (aOR 2.63 [95% CI, 1.06-6.50]). Most respondents (80%) were confident about their hospital being equipped to efficiently rollout COVID-19 vaccines to the general population. While overall attitudes towards COVID-19 vaccination were positive among HCWs in India, acceptance was lower among healthier and younger HCWs. Data availability on vaccine safety and effectiveness, and cost considerations were important for acceptance. Targeted interventions are needed to improve vaccine acceptance amongst HCWs, since they are critical in promoting vaccine acceptance amongst the general population.